Hydrometer in use for water sample testing - Dearborn Chemical Company; The Fensholt Company (1930)
General view of Dearborn Chemical Company employee C.B. Smith utilizing a concentration hydrometer during a water sample field test. Assorted glassware and a Dearborn portable testing cabinet are also visible on the table. A stamp on the verso of the photograph for "The Fensholt Company," a public relations firm based in Chicago, suggests that the photograph was staged for advertising purposes. Founded in 1887, the Dearborn Chemical Company was a corporate ancestor of BetzDearborn, Incorporated best known for manufacturing water treatment chemicals for use in boilers and cooling towers.
Keywords: Employees; Chemical industry; Dearborn Chemical Company; Water purification chemicals industry; Corporations; Hydrometer; Glassware; Scientific apparatus and instruments; Water--Testing; Water--Analysis